Chronic mitral regurgitation in women with coronary heart disease and post-infarction cardiosclerosis - V. A. Kuznetsov; E. I. Yaroslavskaya; G. S. Pushkarev; D. V. Krinochkin; I. P. Zyryanov; L. V. Mar’ynskikh (Российский кардиологический журнал)
Aim. To identify whether mitral regurgitation (MR) is associated with coronary stenosis localisation in women with coronary heart disease (CHD) and postinfarction cardiosclerosis. Material and methods. Among 15283 patients included in the “Coronary Angiography Register” © from 1991 to 2012, the women with CHD and postinfarction cardiosclerosis (age 31–72 years) were selected: 94 without MR and 53 with moderate or severe MR. Results. Patients with MR were significantly older (mean age 57,6±8,5 vs. 52,2±8,5 years; p=0,001), had higher NYHA classes (III–IV) of chronic heart failure, CHF (46,2 vs. 18,5%; p=0,001), and a higher prevalence of repeat myocardial infarction (22,6 vs. 7,1%; p=0,010) than the patients without MR. According to echocardiography data, MR patients demonstrated higher values of left ventricular (LV) asynergy (28,7±14,7 vs. 22,4±12,2%; p=0,016) and linear cardiac dimension indices, including LV indices (30,7±3,0 vs. 27,2±2,7 mm/m 2; p<0,001). This clinical group also shown a reduction inLVcontractility (54,7 vs. 17,9%; p<0,001). MR patients were also characterised by multiple localisation of post-infarction cardiosclerosis (33,3 vs. 17,4%; p=0,035). According to coronary angiography data, stenosis of left coronary artery trunk was observed only in women with MR (9,4 vs. 0%; p=0,008). Multivariate analyses demonstrated an independent association between MR, higher NYHA classes, and increasedLVdimension indices. Conclusion. In women with CHD and post-infarction cardiosclerosis, moderate and severe chronic MR was associated with higher NYHA classes of CHF and increasedLV dimension indices.